THE QUALITIES OF WOMAN AS CHARACTERIZATION IN JOHN STEINBECK’S THE PEARL - Biekaeksi Sri Evanty Mona Amelia Wati; Eko Budi Setiawan (Universitas Katolik Widya Mandala Surabaya, 2020)
This research aimed to (1) find out the qualities of woman as characterizationportrayed in the main female character, Juana and (2) explain how they influenceKino’s character development in John Steinbeck’s The Pearl. To analyze the data,this research used qualitative method. The data of the research were theexpression related to (1) the qualities of woman as characterization portrayed bythe main female character, Juana, and (2) how they influence Kino’s characterdevelopment in the work of John Steinbeck’s The Pearl. The results of thisresearch show the qualities of woman portrayed by the main female character,Juana and how they influence Kino’s character development. Juana, is portrayedas a woman having characterization such as being responsible, strong, loyal andcaring, responsive (including the action she does) and so forth.The qualities ofwoman possessed by Juana as her characterization in the novel seems to givemore courage and motivation, convince him to do more as a husband, and offersuch a strong intuition to deal with problems so that he could consider andreconsider the action he is about to take.